Imaging and radiation isocentre determination for inline MR-guided radiotherapy systems – proof of principle using MR-phantom with embedded monolithic silicon detector. (October 2020) - Causer, T J; Alnaghy, S J; Alnaghy, S; Roberts, N; Petasecca, M; Rosenfeld, A B; Metcalfe, P; Oborn, B M
Abstract: Multiple vendors are now offering real-time MRI-guided radiotherapy systems. Quality assurance of the imaging and radiation isocentre alignment is an essential component of the QA programme for any linear accelerator used for delivering image-guided radiotherapy. In this work, the authors describe the design and feasibility testing of a device that combines a high resolution monolithic silicon strip detector with an MRI visible phantom for characterisation of optical, MR imaging and radiation isocentre for inline MR-guided radiotherapy systems.